Pemberdayaan Ekonomi Perempuan Melalui Pelatihan Koperasi di Kelompok Tani Hutan SHK Lestari Desa Cilimus: Women's Economic Empowerment through Cooperative Training at SHK Lestari Forest Farmers Group, Cilimus Village - Sasora, Fajar; Nelson, Nelson; Kusumastuti, Henni; Dewi, Lies Kumara; Rauf, Eka Ubaya Taruna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This community service aims to empower women in Cilimus Village, especially members of the SHK Lestari Forest Farmers Group Association, through cooperative training. This activity is expected to increase women's understanding and skills in managing cooperatives as sustainable collective economic platforms. The main focus of the training includes cooperative management, cooperative formation, and effective financial management. With this empowerment, women are expected to have a more significant role in improving family and community welfare, while supporting sustainable forest management. This training is expected to create a model of local economic independence that can strengthen the economic and social resilience of communities in the Cilimus Village area.